Alternative Growth and Defensive Strategies Reveal Potential and Gender Specific Trade-Offs in Dioecious Plants Salix paraplesia to Nutrient Availability - Jiang, Hao; Zhang, Sheng; Lei, Yanbao; Xu, Gang; Zhang, Dan (Frontiers in Plant Science, 2016)
Population sex ratios of many dioecious plants in nature are biased. This may be attributed to sexually different resource demands and adaptive capacity. In male-biased Populus, males often display stronger physiological adaptation than females. Interestingly, Populus and Salix, belonging to Salicaceae, display an opposite biased sex ratio, especially in nutrient-poor environmental conditions. Do female willows have a greater tolerance to nutrient deficiency than males? In this study, we investigated the growth and defensive strategies of Salix paraplesia cuttings, which were grown with high and low soil fertility for about 140 days over one growing season. Results suggest that different strategies for biomass allocation may result in sexually different defence capacities and trade-offs between growth and defence. Females are likely to adopt radical strategies, overdrawing on available resources to satisfy both growth and defence, which seems to be more like a gamble compared with males. It is also suggested that females may have an extra mechanism to compensate for the investment in growth under nutrient-poor conditions. In summary, the results may help focus restoration efforts on sex selection such that a moderate increase in female willow quantity could increase the resistance and resilience of willow populations to early sporadic desertification.